2013
DOI: 10.1039/c2ra22508e
|View full text |Cite
|
Sign up to set email alerts
|

A novel benzoxazine/bismaleimide blend resulting in bi-continuous phase separated morphology

Abstract: A novel modified polybenzoxazine with bi-continuous phase separated morphology was successfully prepared from the blend of bisphenol A-aniline benzoxazine (BA-a), N,N9-(2,2,4-trimethylhexane-1,6-diyl)bismaleimide (TBMI) and catalyst imidazole. The thermal and toughness properties of the phase-separated blend cast were improved compared with polybenzoxazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Besides, Takeichi et al prepared a novel type of polymer alloys using traditional benzoxazine and BMI 32 . Gu et al reported a blend of benzoxazine and BMI using imidazole as catalyst 33 . Although the thermal and mechanical properties of benzoxazine/BMI blends have been discussed in detail, the synthesis of quinoxaline‐containing trismaleimide and its polymer alloys with benzoxazine has not been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Takeichi et al prepared a novel type of polymer alloys using traditional benzoxazine and BMI 32 . Gu et al reported a blend of benzoxazine and BMI using imidazole as catalyst 33 . Although the thermal and mechanical properties of benzoxazine/BMI blends have been discussed in detail, the synthesis of quinoxaline‐containing trismaleimide and its polymer alloys with benzoxazine has not been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…However, accompanied with its growing usage, people found that polybenzoxazine prepared from benzoxazine monomer is often very brittle. 9 12 This is attributed to the numerous inter- and intramolecular hydrogen bonds that interfere with the propagation of ring-opening polymerization (ROP). 13 15 This causes a very low cross-linking density but high elastic modulus at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase of the melt viscosity from the high molecular weight gives rise to deterioration in the processability of the benzoxazines, and synchronously this method hampers the thermal properties and strength. The third method is to form multiphase structures by reaction-induced phase separation (RIPS) in benzoxazine/thermoplastic [33][34][35] or benzoxazine/thermosetting [36][37][38][39] systems. The toughening effect of this method is obvious, but it is difficult and complicated to control the formation of different phase structures, especially the prospective multiphase structure during actual production.…”
Section: Introductionmentioning
confidence: 99%